Development of aptamers for rapid airborne bacteria detection - Jeong, In Hwa; Kim, Ho Kyeong; Kim, Hye Ri; Kim, Jungbae; Kim, Byoung Chan (Springer Verlag, 2022)
Airborne microbes can rapidly spread and cause various infectious diseases worldwide. This necessitates the determination of a fast and highly sensitive detection method. There have been no studies on receptors targeting Citrobacter braakii (C. braakii), a pathogenic bacterium which can exist in the air. In this study, we rapidly isolate an aptamer, a nucleic acid molecule that can specifically bind to C. braakii by centrifugation-based partitioning method (CBPM) reported previously by our groups as omitting the repeated rounds of binding incubation, separation, and amplification that are indispensable for SELEX. The binding affinity and specificity of isolated aptamers are checked using bacteria in liquid culture and recollection solution from aerosolized bacteria. Recollection solutions of the recovered bacteria are obtained by nebulizing, drying, and recapturing with a biosampler. The CB-5 aptamer shows high affinity and specificity for C. braakii (K-d: 16.42 in liquid culture and 26.91 nM in recollection from aerosolized sample). Our results indicate the current protocol can be employed for the rapid development of reliable diagnostic receptors targeting airborne bacteria.